Hsp60 as a Novel Target in IBD Management: A Prospect - Cappello, Francesco; Mazzola, Margherita; Jurjus, Abdo; Zeenny, Marie-Noel; Jurjus, Rosalyn; Carini, Francesco; Leone, Angelo; Bonaventura, Giuseppe; Tomasello, Giovanni; Bucchieri, Fabio; Conway de Macario, Everly; Macario, Alberto J. L. (Frontiers in Pharmacology, 2019)
Inflammatory bowel disease (IBD) encompasses various pathological conditions similar but distinct that share a multifactorial etiology, including involvement of the intestinal barrier function, the immune system, and intestinal microorganisms. Hsp60 is a chaperonin component of the chaperoning system, present in all cells and tissues, including the intestine. It plays important roles in cell physiology outside and inside mitochondria, its canonical place of residence. However, Hsp60 can also be pathogenic in many conditions, the Hsp60 chaperonopathies, possibly including IBD. The various clinico-pathological types of IBD have a complicated mix of causative factors, among which Hsp60 can be considered a putatively important driver of events and could play an etiopathogenic role. This possibility is discussed in this review. We also indicate that Hsp60 can be a biomarker useful in disease diagnosing and monitoring and, if found active in pathogenesis, should become a target for developing new therapies. The latter are particularly needed to alleviate patient suffering and to prevent complications, including colon cancer.